The use of lytic plasmid-associated sex pilus-specific bacteriophages to drive microbial evolution towards loss of virulence - Chit-opas, Visara (2021)
Due to an increasing of antibiotic resistance prevalence, several alternatives to antibiotics have been considered, including bacteriophages. This project investigates the potential of sex pilus-specific phage MS2 to drive loss and horizontal transfer of virulence plasmids from E. coli. The study assessed new E. coli host range of phage MS2, determining the natural transfer rate of pHaemolysin, pColicin V and F plasmids, and investigating the impact of phage infection on the virulence plasmids. Phage MS2 could not infect or replicate on the E. coli strains assessed in this study. The horizontal transfer rate of the pHaemolysin and pColicin V plasmids was negligible. Expression of the F pili would be essential for phage susceptibility and bacterial conjugation. Therefore, it is essential to investigate level of the F pili expression within the virulence plasmids. In conclusion, there is a potential limitation in using F pilus-specific bacteriophage to drive loss of virulence plasmids and this we propose this is due to low level of F pili expression and phage susceptibility.